Beyond anti-welfarism and feminist social media mud-slinging: Jo Littler interviews Angela McRobbie. (February 2022) - Littler, Jo; McRobbie, Angela
In this wide-ranging interview, which took place in spring 2021, Angela McRobbie talks about her work in relation to social politics, the contemporary conjuncture, cultural studies, decolonisation and feminism. Beginning with a discussion on her experience of Covid, it contextualises these reflections through a discussion of anti-welfarism and the scapegoating of dependency, drawing from her new book Feminism and the Politics of Resilience . It moves on to discuss different forms and experiences of feminism: including the neoliberal Anglo-German academic context; the legacies of queer theory and radical feminism; the 'mud-slinging' of social media which 'does not allow us the time and space to rehearse what is really going on'; the need to engage with social policy alongside cultural theory; and the ongoing intersectional work of rewriting the curriculum.